A comparative evaluation of the role of olfaction in attachment - Emma Cox; Courtney Collins-Pisano; Lane Montgomery; Jeffrey S. Katz (Animal Cognition)
Abstract Olfactory information plays an important role in the attachment and bonding processes for both humans and non-human animals. Odor cues obtained via individual body odor facilitate attachment and bonding processes across species with regard to both mate selection and mother-infant bonding. The purpose of the present paper is to summarize the role of odor as it pertains to bond formation and maintenance in the mother-infant bond for human infants and non-human animal infants, and for mate selection among human adults and non-human animals. We then synthesize this summary with literature on attachment and existing evidence for the relationships between olfaction and attachment processes. Finally, we suggest avenues for areas of future research.